Game Theory Paradigm: A New Tool for Investigating Social Dysfunction in Major Depressive Disorders - Wang, Yun; Yang, Liu-Qing; Li, Shu; Zhou, Yuan (Frontiers in Psychiatry, 2015)
Social dysfunction is a prominent source of distress and disability in patients with major depressive disorder (MDD) but is commonly omitted from current clinical studies, although some researchers propose an evolutionary strategy to understand these negative outcomes. Limited knowledge about the neural basis of social dysfunction in MDD results from traditional paradigms, which lack insights into social interactions. Game theoretical modelling offers a new tool for investigating social interaction impairments in neuropsychiatric disorders. This review first introduces three widely-used games from game theory and the major behavioral and neuroimaging findings obtained using these games in healthy populations. We also address the factors that modulate behaviors in games and their neural bases. We then summarize the current findings obtained by using these games in depressed patients and discuss the clinical implications of these abnormal game behaviors. Finally, we briefly discuss future prospects that may further elucidate the clinical use of a game theory paradigm in MDD.